PERCEPTION OF FAMILY FARMERS REGARDING FAMILY FORESTRY PRODUCTION - Farias, Jorge Antonio; Badin, Tiago Luís; Bernardy, Daniele; Ziembowicz, Matheus Morais; Souza, PABULO DIOGO (Floresta, 2024)
Forest plantations in family farming play an important role in meeting the energy needs of rural properties. In this context, the objective of this study was to analyze the characteristics related to the perception of rural producers regarding family forestry production. Data collection consisted of interviews with 434 rural producers between 2013 and 2014. These interviews were based on topics that reflect the producers' perception of family forestry production, and the vast majority have been cultivating forests for more than a decade. It became evident that there is little influence from public agents in training and capacity-building for family forestry production. The choice of species and spacing is based on empirical knowledge, and rural properties have a deep connection with forestry production. However, producers lack knowledge regarding the management techniques of these forest plantations.